ANALISIS PERAN WAKAF LAHAN DALAM PENGEMBANGAN INFRASTRUKTUR SOSIAL: STUDI KASUS PEMBANGUNAN MASJID-MUSHOLA DI KECAMATAN LECES - Fasil, Maulana Rihdo Al; Fida , Imanuddin Abil (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to analyze the role of waqf land in the development of social infrastructure, with a focus on the construction of mosques and prayer halls in the Leces District. A mixed-methods research methodology is employed to gain a comprehensive understanding of the perspectives, motivations of waqf donors, influencing factors, and the utilization process of waqf land for mosques and prayer halls. Quantitative data is obtained through surveys and statistical analysis, while qualitative data is gathered through interviews and observations. The results of this research are expected to provide in-depth insights into the potential and contribution of waqf land to social development in the Leces District and serve as a foundation for the development of more effective policies in managing waqf land. Keyword: waqf; social infrastructure; mosque musalla.